The Influence of Organizational Culture and Work Environment on Employee Engagement Through Employee Resilience as Intervening Variable (Study on Strategic Management and Governance-Bank Indonesia) - Febrianty Lombongadil; Masydzulhak Djamil (Dinasti Publisher, 2023)
The purpose of this study was to examine the influence of organizational culture and work environment through employee resilience as an intervening variable on employee engagement at Strategic Management and Governance Department - Bank Indonesia. The quantitative descriptive research design with 92 participants as sample of the study. This study used Partial Least Square (PLS) which is a covariance-based SEM as an analysis tool. The result of this study showed that (1) organizational culture influences employee engagement positively and significantly (2) organizational culture has a positive and significant effect on employee resilience, (3) work environment influences employee engagement positively but not significantly (4) work environment influences employee resilience positively and significantly (5) Employee resilience has positive and significant effect on employee engagement (6) Employee engagement is positively and significantly influenced by organizational culture through employee resilience (7) Employee engagement is positively and significantly influenced by the work environment through employee resilience. The implementation of organizational culture and the work environment’s condition at Bank Indonesia must be improved. These variables also affect the level of employee engagement. The higher level of employee engagement will help the employee to complete the duties and obligations optimally and properly.